Superare Parmenide: Zenone, Melisso e Gorgia impegnati a fare ‘meglio di lui’ - Rossetti, Livio (Revista Archai, 2021)
During the fifth century BCE Parmenides had many and qualified readers, among whom Zeno, Empedocles, Anaxagoras, Leucippus, Melissus, Protagoras, Gorgias, Hippias. Three of them tried to do much more than what he was able to do with the ‘deductive exercise’ we encounter in 28B8.1-33 (or, in the case of Melissus, with the whole doctrine of being), and they succeeded. Indeed, that they strived to overcome the high standard already reached by Parmenides in the invention of strictly deductive passages is basically out of the question. My paper is devoted to account for the ambitious aims Zeno, Melissus, and Gorgias attained, each in a very distinguished manner.